PERANPEREMPUANDALAMPENINGKATANPRODUKTIVITASEKONOMIRUMAHTANGGADIDESAWISATAPANDANREJOKALIGESINGPURWOREJO - Heri Wibowo (STIE Rajawali Purworejo, 2023)
TheobjectivestobeachievedbyobserversintheresearcharefirsttoimprovethewelfareofwomeninincreasinghouseholdeconomicproductivityinPandanrejovillage.Second,toincreasethebeautyofGunungGajahvillagetourismwhichiscrowdedwithvisitorsandtoincreasethewelfareofthevillage.Third,tocreatebeautyandpreservenature.Thisresearchwascarriedoutthroughanassessmentprocessbasedonresearchcoveringfourstages:planning,implementation,observation,reflection.Fortheresultsoftheanalysisandinitialstudyoftheroleofwomenwhosucceededinincreasingtheeconomicproductivityofvillagehouseholds,therewas35%villagetourism(10-15people).Aftertheinvolvementandimportantroleintheinitialtouristvillage,thetourismopeningbecame50%(25people)andbecame75%(35people).Thus,itcanbeconcludedthattheexistenceoftheGunungGajahKaligesingtourismvillageinPurworejocanincreasetheroleofwomeninhouseholdeconomicproductivityinPandanrejoVillage.